Implementasi Model Pembelajaran Kooperatif TGT Melalui Pendekatan Taktis Keterampilan Bermain Bola Voli Mini dan Kepercayaan Diri Siswa Sekolah Dasar - Aulia Rahma; Agus Mahendra; Eva Sri Gumilang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the effect of implementing the cooperative learning model Teams Games Tournament (TGT) through a tactical approach on mini volleyball playing skills and self-confidence of elementary school students. This research used a quantitative approach with a quasi-experimental method and a nonequivalent group pretest-posttest design, involving 40 fifth-grade students of SDN 062 Ciujung divided into an experimental group and a control group through purposive sampling technique; data were collected using the Game Performance Assessment Instrument (GPAI) and a self-confidence questionnaire, then analyzed using the Wilcoxon Signed Rank Test, Mann-Whitney U Test, and Paired Samples T-Test. The results showed that (1) the TGT model through a tactical approach had a significant effect on improving mini volleyball playing skills (Sig. = 0.000); (2) the model had a significant effect on students' self-confidence (Sig. = 0.000); so it can be concluded that this learning model is effective to be applied as an alternative learning strategy for Physical Education, Sport, and Health in elementary schools. Keywords: Elementary School, Mini Volleyball, Self-Confidence, Tactical Approach, TGT Model